PENGARUH PENDEKATAN PROBLEM POSING DAN CTL TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA BAGI SISWA SMA - Shanti, Widha Nur; Sholihah, Dyahsih Alin; Abdullah, Ahmad Anis (Jurnal Karya Pendidikan Matematika, 2018)
This study aims to determine the effect of the Problem Posing approach and the Contextual Teaching and Learning (CTL) approach to critical thinking skills. This study is a quasi-experimental study with randomize design pretest-posttest control group design. The population of this study were all class X students of SMA Negeri 1 Sentolo consisting of six classes. From the population, two classes were randomly sampled as the research sample, namely class X MIA 3 and class X MIA 1. In class X MIA 3 students applied learning using the Problem Posing approach and class X MIA 1 students used the CTL approach. The instrument used to collect data is a test of critical thinking skills. To examine the effect of the Problem Posing approach and the CTL approach on critical thinking ability data were analyzed using the t test. The results showed that there were differences in the ability to think critically between classes with learning using the Problem Posing approach and the classroom with learning using the CTL approach, with the average students critical thinking skills in the class with the Problem Posing approach higher than the students critical thinking skills. in the class with the CTL approach.